EKSISTENSIALISME TOKOH UTAMA DALAM NOVEL MALIOBORO AT MIDNIGHT KARYA SKYSPHIRE - Deni Arifiyanto; Eko Cahyo Prawoto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
Existentialism is a school of philosophy that states humans as beings who have actuality that is tangible and stands for itself. Existentialism was used as a theory to dissect Skysphire's novel Malioboro at Midnight. The purpose of this study is to describe the forms of existentialism. This research data is in the form of words, clauses, sentences and expressions that show forms of existentialism using the theory of Jean Paul Sartre. The source of this research data is the novel Malioboro at Midnight by Skysphire published in 2023. The data were analyzed using qualitative descriptive methods.  Data is obtained by reading and interpreting. The validity of the data in this study was obtained through trianggulation of theories and methods. In this study, existentialism was found in the form of Etre Pour Soi and Etre En Soi.